Identification of the novel HLA‐DPB1 allele, HLA‐DPB1*1326:01, in an Italian bone marrow donor. (11th October 2022) - Biagini, Chiara; Fornaciari, Silvia; Lamanna, Roberta; De Gregorio, Veronica; Curcio, Michele
Abstract : The novel HLA class II allele HLA ‐ DPB1 * 1326 : 01 is described.